DUAL APPROACH FOR MODELLING DEMAND SATURATION LEVELS IN THE AUTOMOBILE MARKET. THE GOMPERTZ CURVE: MACRO VERSUS MICRO DATA - Felis Rota, Marta; Moral Carcedoa, Julián; Pérez García, Julián (Investigación Económica, 2016)
We propose the use of a dual approach for modelling the saturation levels in the automobile market. We combine macro data coming from a pool of observations corresponding to the vehicle fleet and per capita income in a broad set of countries, with micro data coming from the Survey of Household Finances, elaborated by the Banco de España (Bank of Spain) for the Spanish case. This double approach estimation allows taking advantage of both types of data, so that the results can be complemented for a more detailed understanding of the automobile market. Macro data capture the dynamics inherent to the process of diffusion in the automobile market as income per capita rises. Micro data are not affected by socio-institutional disparities at the country level and, at the same time, offer a much more detailed level of information in terms of vehicle owner characteristics.